1986
DOI: 10.1152/ajprenal.1986.250.5.f917
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine alters glomerular filtration control by angiotensin II

Abstract: This study was designed to test the hypothesis that high renal levels of adenosine (ADO) may alter glomerular filtration rate (GFR) control by angiotensin II (ANG II). In normal kidneys, ANG II infusion (20 ng X kg-1 X min-1 iv) decreased renal blood flow (RBF) to 61 +/- 3% of control, increased filtration fraction (FF) to 173 +/- 21% of control, and did not change GFR significantly. During intrarenal ADO infusion at a rate of 1.0 mumol/min, ANG II (20 ng X kg-1 X min-1 iv) decreased RBF and GFR to 61 +/- 5 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
24
1

Year Published

1992
1992
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 0 publications
3
24
1
Order By: Relevance
“…Consistent with previous reports (Hall and Granger, 1986;Aki et al, 1990), the present data showed that intrarenal infusion of adenosine evoked a transient reduction in renal blood flow that rapidly waned, with renal blood flow returning to a value above the control level. We also observed that renal blood flow was further increased after addition of KW-3902 to adenosine infusion.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with previous reports (Hall and Granger, 1986;Aki et al, 1990), the present data showed that intrarenal infusion of adenosine evoked a transient reduction in renal blood flow that rapidly waned, with renal blood flow returning to a value above the control level. We also observed that renal blood flow was further increased after addition of KW-3902 to adenosine infusion.…”
Section: Discussionsupporting
confidence: 93%
“…The results from the present study confirm previous observations that renal vasoconstrictor actions of angiotensin II were augmented by intra-arterial infusion of exogenous adenosine in anesthetized dogs (Hall and Granger, 1986). Furthermore, the present data extend these observations to indicate that adenosine also augments norepinephrine-induced renal vasoconstriction.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3 -3 -911 The proposed role of adenosine is unique among these substances in that local production of this compound is postulated to accentuate rather than attenuate vasoconstrictor responses to Ang II. For example, Hall and Granger 5 reported that intrarenal adenosine infusion alters the influence of Ang II on glomerular function in the dog in a manner consistent with an unmasking of a preglomerular vasoconstrictor effect of Ang II. These investigators proposed that prevailing interstitial adenosine levels may be an important determinant of afferent arteriolar Ang II responsiveness, whereas efferent responses to Ang II appear to be adenosine independent.…”
mentioning
confidence: 99%
“…3 - 5 Such observations have led to the suggestion that the effects of Ang II on afferent and/or efferent arterioles might be modulated by the action of an endogenously produced substance. The substances proposed to modulate renal microvascular Ang II responsiveness include vasodilator prostaglandins, 6 -7 endothelium-derived relaxing factor, 8 and adenosine.…”
mentioning
confidence: 99%